1984
DOI: 10.1152/ajpheart.1984.246.4.h508
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of rhythmic diameter changes in arterial microcirculation

Abstract: The diameter of the arterial and arteriolar blood vessels was measured as a function of time in the hamster skin fold window preparation. When the animals recovered from the surgical implantation, the diameters of the arterial microvessels exhibited a continuous rhythmic activity throughout the preparation for a period of 2 wk while the chamber was intact. The amplitude of the diameter changes was directly proportional to the mean vessel size. The frequency of this phenomenon was determined by power spectrum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 0 publications
9
152
0
1
Order By: Relevance
“…The study was approved by the local Animal Subjects Committee of the University of California, San Diego. The window chamber model is widely used for microvascular studies in the unanesthetized state, and the complete surgical technique is described in detail elsewhere (3,10). This model was used to maintain the catheters in place in the awake animals and to prevent them from chewing or pulling them.…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the local Animal Subjects Committee of the University of California, San Diego. The window chamber model is widely used for microvascular studies in the unanesthetized state, and the complete surgical technique is described in detail elsewhere (3,10). This model was used to maintain the catheters in place in the awake animals and to prevent them from chewing or pulling them.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneous rhythmic oscillations in vessel diameter are known as vasomotion and occur primarily in small arteries and arterioles (Bertuglia et al, 1996;Colantuoni et al, 1984Colantuoni et al, , 1990Jackson et al, 1991;Meyer et al, 1988;Meyer & Intaglietta, 1987;Schmidt et al, 1993;Slaaf et al, 1987;Wiedeman, 1955). Generally, the frequencies of the oscillations are in the range 3-30 min −1 and the peak-peak amplitudes are large, 50-100% or more of the mean diameter (Tuma et al, 2008).…”
Section: The Phenomenon Of Vasomotionmentioning
confidence: 99%
“…The oscillations varied in frequency and duration and appeared independent of other vessels. Colantuoni et al (1984) studied vasomotion in several different vessel types in a hamster skin fold window preparation. They showed that the oscillations were independent of the nervous system and that the fundamental c The Author 2011.…”
Section: The Phenomenon Of Vasomotionmentioning
confidence: 99%
“…The hamster window chamber model is widely used for microvascular studies in the unanesthetized state, and the complete surgical technique is described in detail elsewhere. 15,16 Catheters were tunneled under the skin, exteriorized at the dorsal side of the neck, and securely attached to the window frame.…”
Section: Animal Preparationmentioning
confidence: 99%